Los servicios de interés general en la Unión Europea - Laguna de Paz, José Carlos (Pontificia Universidad Católica del Perú. Fondo Editorial, 2016)
(i) Since the eighties, the European Union has implemented a policy aimed to achieve that the services of general economic interest are truly integrated in the internal market. To this end, European regulation has liberalized and harmonized the legal framework of the main economic sectors. Significant progress towards European integration has been achieved. However, the internal market is still not truly effective. (ii) Conversely, non- economic services are primarily the responsibility of Member States. They are not covered by the internal market rules, although the general provisions of the Treaty are to be applied.

(i) Desde los años ochenta, la Unión Europea ha impulsado la incorporación de los servicios económicos de interés general al mercado interior. Las normas europeas han liberalizado y armonizado el régimen jurídico de los grandes sectores económicos. Se han alcanzado progresos apreciables en la integración europea, pero el mercado interior sigue sin ser una realidad acabada. (ii) En cambio, los servicios sociales son competencia de los Estados miembros. No están sujetos a las reglas del mercado interior, aunque sí a las normas generales del Tratado.
Services of general interest in the European Union
Keywords: Servicios de interés general; Servicios públicos; Regulación; Competencia; https://purl.org/pe-repo/ocde/ford#5.05.00